Application of the LLT pressuremeter test to soil engineering problems in Bangkok clay - Surya, Ibrahim; Brenner, R.P.; Ohta, Hideki; Prinya Nutalaya; The Government of Australia (Bangkok : Asian Institute of Technology, 1981)
The application of a monocell- type pressure meter known as "Lateral Load Tester" (LLT), to foundation engineering problems in the Bangkok area was investigated . In the first part of the study , the influence of the technique for preparing the borehole on certain soil parameters was examined . It was found that the wash boring method using a specially designed drill bit produced the highest values of deformation modulus . On the other hand, the so-called thin-walled tube method in which the hole is created by pushing a thin-walled tube, achieved superior results for evaluating the horizontal earth pressure at rest. In any case, it was demonstrated that the method used for preparing the borehole greatly affects the shape and position of the pressure meter curve from which the soil parameters are derived . In the second part, laboratory test results (from unconfined compression and UU tests) and field test results (from the vane and Dutch cone) were compared and correlated with pressure meter test data. It was found that the shear strength derived from the pressure meter curve was considerably larger than that obtained from laboratory strength tests or vane shear tests. Good correlations were found between net limit pressure and vane shear strength and also between limit pressure and cone resistance. Finally, in a third part, various calculation methods for predicting deformations and ultimate load of piles and the settlement of embankments were applied using the soil parameters determined by the LLT procedure. While the methods developed by Menard for predicting the ultimate capacity of vertically loaded piles and the settlement of embankments resulted in considerable differences with the observed values, better predictions for pile settlements were obtained from Cassan's method. For estimating the deflection of a laterally loaded pile, Yoshida & Yoshinaka 1 s method resulted in good agreement with the measured value
A thesis submitted in partial fulfilment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M. Eng.) - Asian Institute of Technology, 1981
Keywords: Soil consolidation test